Boosting Students Grammar Achievement Applying Johnny Grammar Word Challenge Application In Senior High School - Khoirunnisa, Khoirunnisa; Supriyono, Supriyono (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This paper intends to figure out the effectiveness of Johnny Grammar Word Challenge in boosting students grammar achievement at senior high school. quantitative approach with Pre- experimental design with one group of Pre-Test and Post-Test is used to design this research. The research subject of this study was X-B grade students of SMAN 1 Kesamben in academic year 2022/2023 selected by purposive sampling technique. 35 questions is used to design the research insrument. The data was analyzing by using SPSS 25.0 version. The result shows, that there is significant difference scores on students’ grammar achievement especially in Irregular verb after being used by Johnny Grammar Word Challenge. The mean value increase from 68 up to 81. Thus, the researchers suggest teachers to use it as a other variation in teaching English subject.